Pelatihan Pembuatan Pupuk Kompos pada IKM ARG Desa Pesawahan Kabupaten Garut - Suhartini, Suhartini; Irawan, Candra; Sukiman, Maman; Rosalina, Rosalina; Utami, Andita; Putri, Imalia Dwi; Septian, Wira Aditia; Azhar, Kheiza Noor Aulia; Alhafish, Muhammad Radhi; Pramudya, Muhammad Kemal Caesar Aqidah (Jurnal Pengabdian Masyarakat AKA, 2023)
Livestock waste is still a problem that demands government attention. One of the livestock wastes that cause pollution comes from the cultivation of rabbits. The variation in the number of processed rabbits causes an increase in demand for the number of rabbits, which will be proportional to the amount of waste produced, both in the form of manure and leftover feed. One of the efforts to control rabbit farm waste can be done by processing it into compost. This community service activity aims to provide skills in making compost made from manure and rabbit feed to the Pesawahan Village community, who are members of IKM ARG using Effective Microorganism 4 (EM4) and Trichoderma activators. Training activities are carried out through three stages, namely pre-implementation which includes an initial survey and situation analysis, the implementation stage which consists of outreach and composting training, and evaluation of the results of activities. The results of the training showed that the compost from the training was smoother and moister than the IKM ARG fertilizer before the training was given. Based on the results of the questionnaire, it is known that IKM ARG members are interested in applying the results of the training to produce compost.